Elevating Maritime Competence: A Qualitative Analysis of Semester 3 Cadets' Perspectives at Maritime Institute Jakarta (STIP Jakarta) - Marudut Bernadtua Simanjuntak (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
This research delves into the intricate realm of maritime education, focusing on the academic and professional preparedness of Semester 3 cadets at the Maritime Institute Jakarta (STIP Jakarta). Anchored in a qualitative descriptive approach, the study synthesizes document analysis and cadet surveys to unravel the multifaceted dynamics shaping the educational landscape. The document analysis reveals a curriculum at STIP Jakarta that aligns commendably with international standards, supported by comprehensive lecturer training programmes. However, the nuanced cadet perspectives spotlight a need for refined emphasis on the practical application of English proficiency in real-world maritime scenarios. Cadet self-assessment underscores both confidence in academic intelligence and an identified need for additional language support, calling for targeted interventions. Exploring professional competences uncovers a disparity between technical proficiency and English Maritime communication, highlighting the importance of a holistic approach to bridge this gap. Cadet motivations vary from a genuine passion for maritime activities to the allure of lucrative career prospects and international recognition. Recognizing this diversity urges the need for personalised career guidance and mentorship programmes. The research also sheds light on English Maritime and Literacy proficiency, differentiating between basic skills and the ability to handle complex communication scenarios. Recommendations include integrating advanced language modules and tailored language support initiatives within the curriculum, ensuring a seamless development of linguistic skills alongside technical competences. In conclusion, this research offers a comprehensive understanding of maritime education at STIP Jakarta, unveiling challenges and opportunities that resonate globally. The synthesis of findings and recommendations forms a compass for refining pedagogical approaches, fostering linguistic and technical adeptness in future maritime professionals. This voyage towards enhancement is not merely a localized pursuit but a contribution to the broader discourse on cultivating global competence in maritime education.